Assessment of quail meat nuggets prepared with ocimum gratissimum extract (2018)
Consumers today demand foods with high nutritional value that are free from chemical preservatives. Ocimum gratissimum extract (OGE) was used as an antimicrobial agent and natural preservative at graded levels to assess the quality of nuggets made from Japanese quail meat. Batches of nuggets were produced from meat obtained from thirty-six (36) spent quails divided into four treatments (T1-0%, T2-2%, T3-4%, and T4-6%) in a completely randomized design. Carcass characteristics and physico-chemical parameters of fresh quail meat, prior to assigning to treatments were determined. Prepared quail meat nuggets were analysed for pH, proximate composition, cooking loss/yield, microbial and sensory characteristics. Results showed that mean live weight, carcass weight and dressing percentage of quail carcass were 144.00±10.17, 92.83±2.57 and 64.72±3.75, respectively while mean pH, water holding capacity, meat swelling capacity and extract release volume of fresh quail meat were 6.07±0.12, 70.27±5.24, 85.30±6.75 and 32.00±3.46, respectively. There were no significant differences (p>0.05) in pH, cooking yield and cooking loss of quail meat nuggets across the treatments. Highest values were however obtained for T4 (6.39), T2 (78.87) and T3 (30.45) in pH, cooking yield and cooking loss, respectively. Proximate composition of quail meat nuggets varied significantly (p<0.05) across the treatments with values ranging from 60.45 – 64.05 for moisture, 14.65 – 17.40 for protein and 10.85 – 12.30 for fat. Low microbial load counts were obtained in all treatments with T4 having lowest counts for total plate and coliform while T2 had the lowest count for yeast and mould. Low consumer acceptability scores were however obtained for all treatments. It was concluded that increasing the inclusion rate of OGE up to 6%, gave better quality quail meat nuggets.